West Indian identity construction through three main characters in the novel La Vie Scélérate of Maryse Condé - Ulloa Aguilar, Renato (2025)
This article aims to provide a general overview of the process of identity construction in postcolonial French-speaking West Indian literature; particularly in the work of the Guadeloupean writer Maryse Condé. Through various theoretical approaches, we analyze the physical and moral characteristics of the three main characters of the book La Vie Scélérate in order to find the identity traits characteristic of West Indian society.